he effect of training load during the month of Ramadan in the competition phase on Rating of Perceived Exertion, the performance of Sprint and Maximal Aerobic Speed for senior soccer players. - جيلالي قاضي; محمد الامين بارودي; الغوتي مازوز (Journal of Sport Science Technology and Physical Activities, 2025)
The aim of this study was to investigate the effect of fasting during the month of Ramadan on the performance of sprint and maximum aerobic speed (MAS) in Algerian football for senior soccer players. For this purpose, the researchers used a experimental method on a sample of 18 players who were selected purposively. We relied on a 30m straight line speed test to measure sprint, the Vameval test to measure maximum aerobic speed, and the session rating of perceived exertion (S-RPE) to measure fatigue levels. We relied on the mean, standard deviation, and paired samples t-test for the statistical analysis using SPSS software. The results showed that Ramadan does not have a negative effect on the performance of speed and maximum aerobic speed in football players